2022
DOI: 10.1038/s41598-022-25790-2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of extracellular alpha-synuclein is independent of intracellular alpha-synuclein

Abstract: Parkinson´s disease (PD) pathology progresses throughout the nervous system. Whereas motor symptoms are always present, there is a high variability in the prevalence of non-motor symptoms. It has been postulated that the progression of the pathology is based on a prion-like disease mechanism partly due to the seeding effect of endocytosed-alpha-synuclein (ASYN) on the endogenous ASYN. Here, we analyzed the role of endogenous ASYN in the progression of PD-like pathology in vivo and in vitro and compared the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…In fact, αSyn aggregates spread between interconnected brain areas in a cell-to-cell and prion-like fashion which involve neurons and non-neuronal cells [58,59]. Transsynaptical transmission of aSyn may be triggered by the oligomeric aSyn-mediate microglia activation in the early phases of the disease [60] or by interactions between endogenous aSyn and mitochondria [61,62]. However, cells differentially mediate the uptake of the aSyn fibrils involving processes such as receptor-mediated endocytosis, extracellular vesicles and tunneling nanotubes.…”
Section: αSyn Toxicitymentioning
confidence: 99%
“…In fact, αSyn aggregates spread between interconnected brain areas in a cell-to-cell and prion-like fashion which involve neurons and non-neuronal cells [58,59]. Transsynaptical transmission of aSyn may be triggered by the oligomeric aSyn-mediate microglia activation in the early phases of the disease [60] or by interactions between endogenous aSyn and mitochondria [61,62]. However, cells differentially mediate the uptake of the aSyn fibrils involving processes such as receptor-mediated endocytosis, extracellular vesicles and tunneling nanotubes.…”
Section: αSyn Toxicitymentioning
confidence: 99%
“…Once internalized by recipient cells, aSyn aggregates may induce the misfolding and aggregation of intracellular aSyn, thus perpetuating the cycle of aggregate formation (Masuda‐Suzukake et al, 2013; Paumier et al, 2015). Experiments using aSyn KO mice showed that endogenous aSyn is essential for the spreading of pathology, a process that does not require aSyn toxicity (Dening et al, 2022). Consequently, transmitting aSyn aggregates between cells may contribute to the progression of neurodegeneration observed in PD and related disorders.…”
Section: Introductionmentioning
confidence: 99%